Optimization of Various ITS rDNA Amplification Protocol of Yeast Isolated from Giant Honey Beehives (Apis dorsata) - Choiriyah, S.Si, Chumaidatul; Firdhausi, Nirmala Fitria; Tyastirin, Esti; Rachmawati, Yuanita; Hadi, Moch. Irfan (Jurnal Riset Biologi dan Aplikasinya, 2021)
Indonesia is a country with high variability of microorganisms, including bacteria, yeast, and fungi. Yeast isolates could be isolated from the honeycomb of Apis dorsata. Molecular approaches were used to identify yeast using ribosomal DNA gene sequences, called the ITS gene. The optimum condition for DNA extractions and amplifications are needed for the successfully of molecular identification. Therefore, it is necessary to optimize the DNA extraction and amplification of several protocols to obtain good identification results. This study aimed to compare the effects of DNA extraction with various temperatures and different amplification protocols. LIPI reference DNA extraction protocol with the boiling method and variations in incubation time of 10, 15, and 20 minutes at a temperature of 98° C. Meanwhile, for the amplification of yeast DNA using a variety of different amplification protocols. The results showed the optimal time of incubation was 10 minutes in K1 isolates with DNA purity of 1.896. meanwhile, for isolates K2, K3, and K4 each with a purity of 2.246, 2.335, and 1.748. optimal DNA amplification results were indicated by the presense of DNA bands for each sample K1, K2, K3, and K4, namely 503, 542, 492, and 526 bp. In this study, it can be concluded that the optimal incubation time for the extraction process is 10 minutes. In addition, the optimal amplification protocol was shown in the DNA bands in all sample.